Glomerular Filtration Rate Calculation Based on Serum Creatinin and Cystatin C in Type 2 Diabetic Patients - Thom, Vu Thi; Van Nga, Vu; Thi Quynh, Do; Thi Binh Minh, Nguyen; Thi My Dung, Dinh; Ngoc Thanh, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2019)
The incidence of type 2 diabetes mellitus is rapidly increasing, with many complications pressured on the health care system. Complications of diabetes due to chronic hyperglycemia related to other metabolic disorders, causing damage to the microvascular system. Among them, damaged kidney vessels lead to impair the renal function as diabetic nephropathy is the most common cause of end-stage renal disease. Measurement of glomerular filtration rate (GFR) is an important parameter in assessing renal function. In Vietnam’s hospital, serum creatinine is the biomarker mostly used to assess GFR. However, this biomarker is affected many factors such as gender, age, ... Many studies showed that serum Cystatin C is another biomarker that can detect early decline in GFR, less affected by other factors. Therefore, we conducted this study to explore serum cystatin C and creatinine levels in patients with type 2 diabetes and initially compare GFR in applying formulas of CKD.EPI 2012 and age and sex factors with these two biomarkers on those patient groups. The prospective, descriptive, cross-sectional study was performed on 50 patients with type 2 diabetes. Serum Cystatin C, serum creatinine test was performed and GFR was estimated by CKD.EPI 2012 equation. The results showed that the average serum Cystatin C level of the study group was 0.87 ± 0.24 mg/L that expressed no difference between two genders, and significant difference between age groups. Whereas, the average serum creatinine level of the study group was 81.30 ± 19.70 µmol/L, significant difference between male and female but not difference between age groups. In patients with GFR <60 mL/min/1.73m 2 , serum creatinine and cystatin C levels were higher than normal but there was no difference with the upper limit in the normal reference range of the two indications. Keyword Type 2 diabetes, serum cystatin C, serum creatinine, glomerular filtration rate. References [1] N.H. Cho, J. Kirigia, J.C. Mnanya, K. Ogurstova, L. Gủaiguata, W. Rathmann, G. Roglic, N. Forouhi, R. Dajani, A. Esteghmati, E. Boyko, L. Hambleton, O.L.M. Neto, P.A. Montoya, S. Joshi, J. Chan, J. Shaw, T.A. Samuels, M. Pavkov, A. Reja, IDF Diabetes Atlas eight edition, International Diabete Federation, 2017. http://fmdiabetes.org/wp-content/uploads/2018/03/IDF-2017.pdf (access 15 july 2019). [2] G. Xu, B. Liu, Y. Sun, Y. Du, L.G. Snetselaar, F.B. Hu, W. Bao, Prevalence of diagnosed type 1 and type 2 diabetes among US adults in 2016 and 2017: population based study, British Medical Journal 361 (2018) k1497. https://doi.org/ 10.1136/bmj.k1497. [3] N.T.T. Minh, N.K. Luong, N.K. Son, The clinical and subclinical characteristics in patients with diabetes mellitus treated at Thai Nguyen General hospital, Journal of pratical medicine 787 (2011) 25-8. [4] N.T.H. Lan, L.D. Tuan, Survey characteristics of renal complication in elderly type 2 diabetes outpatients treated at National Hospital of Endocrinology, Journal of Military Pharmaco-medicine 6 2017 55-62. [5] Mohsen Pourghasem, Hamid Shafi, Zahra, Histological changes of kidney in diabetic nephropathy, Caspian J Intern Med 6(3) (2015) 120-7. https://www.ncbi.nlm.nih.gov/pmc/articles/PMC4650785/pdf/cjim-6-120.pdf (access 16 july 2019). [6] D.W. Powell, D.N. Kenagy, S. Zheng, S.C. Coventry, J. Xu, L. Cai, E.C. Carlson, P.N. Epstein, Associations between Structural and Functional Changes to the Kidney in Diabetic Humans and Mice, Life Sci 93(7) (2013) 257-64. https://doi.org/ 10.1016/j.lfs.2013.06.016. [7] Natalie Ebert, Elke Schaeffner, New biomarkers for estimating glomerular filtration rate, Journal of Laboratory and Precision Medicine 3(75) (2018. https://doi.org/10.21037/jlpm.2018.08.07. [8] L.A. Inker, C.H. Schmid, H. Tighiouart, J.H. Eckfeldt, H.I. Feldman, T. Greene, J.W. Kusek, J. Manzi, F.V. Lente, Y.L. Zhang, J. Coresh, A.S. Levey, Estimating Glomerular Filtration Rate from Serum Creatinine and Cystatin C, The new England Journal of Medicine 367 (2012) 20-9. https://doi.org/ 10.1056/NEJMoa1114248. [9] Ashwin Kumar, Anil Kumar, Serum cystatin C and serum creatinine levels in type 2 diabetes mellitus, International Journal of Research in Medical Sciences 3(1) (2015) 174-7. https://doi.org/10.5455/2320-6012.ijrms20150130. [10] X. Jianguo, D.I. Broadhurst, M. Wilson, D.S. Wishart, Translational biomarker discovery in clinical metabolomics:an introductory tutorial, Metabolomics 9 (2013) 280–99. https://doi.org/ 10.1007/s11306-012-0482-9. [11] B.T. Anh, Estimate the glomerular filtration rate by plasma creatinine and cystatin C concentration, Journal of Vietnam Medicine 2 (2012) 12-18. [12] S. Kakde, S. Alexander, V.G. David, S. Jacob, A. Mohapatra, A.T. Valson, B. Gopal, C.K. Jacob, J. Hephzibah, V. Tamilarasi, S. Varughese, Relationship of creatinine and cystatin C-based estimated glomerular filtration rates with measured glomerular filtration rate in healthy kidney donors from South Asia, Indian J Nephrol 28 (2018) 345-50. https://doi.org/ 0.4103/ijn.IJN 249_17 [13] Olympus life science research europa GmbH, Olympus clinical chemistry reagent guide, Olympus Diagnostic, American, 2009. [14] International Society of Nephrology, KDIGO 2012 clinical practice guideline for the evaluation and Management of chronic kidney disease, Kidney Int, Kidney International Supplements 3(1) (2012) 5-14. https://kdigo.org/wp-content/uploads/2017/02/KDIGO_2012_CKD_GL.pdf (access 19 july 2019). [15] American Diabete Association, Classification and Diagnosis of Diabetes: Standards of Medical Care in Diabetes 2018. Diabetes Care, (41(Supplement 1)) (2018) S13-S27. https://diabetesed.net/wp-content/uploads/2017/12/2018-ADA-Standards-of-Care.pdf (access 18 july 2019). [16] L.S. Weinert, A.B. Prates, F.B. do Amaral, M.Z. Vaccoro, J.L. Camargo, S.P. Silveiro, Gender does not influence cystatin C concentrations in healthy volunteers, Clin Chem Lab Med 48(3) (2010) 405-8. https://doi.org/10.1515/CCLM.2010.068. [17] N.T. Ly, T.T.C. Mai, Serum cystatin C and renal function in type 2 diabetic patients, Journal of medical Research 80(3B) (2012) 17-O.Al. [18] Musaimia, A.H. Abu-Nawwas, D.Al. Shaera, N.Y.Khaleela, M.Fawzi, Influence of age, gender, smoking, diabetes, thyroid and cardiac dysfunctions on cystatin C biomarker, Medicina de Familia Semergen 45(1) (2019) 44-51. https://doi.org/ 10.1016/j.semerg.2018.07.005. [19] M.C. Odden, I.B. Tager, R.T. Gansevoort, S.J.L. Bakker, R. Katz, L.F. Fried, et al, Age and cystatin C in healthy adults: a collaborative study, Nephrol Dial Transplant 25(2) (2010) 463-9. https://doi.org/10.1093/ndt/gfp474. [20] E.D. O’ Sullivan, J. Hughes, D.A. Ferenbach, Renal Aging: Causes and Consequences, J Am Soc Nephrol 28 (2017) 407–20. https://doi.org/10.1681/ASN.2015121308. [21] E.D. O’ Sullivan, J. Hughes, D.A. Ferenbach, Renal Aging: Causes and Consequences, J Am Soc Nephrol 28 (2017) 407–20. https://doi.org/10.1681/ASN.2015121308. [22] Christiane Oddoze, Henri Portugal, Yvon Berland, Bertrand Dussol, Cystatin C Is Not More Sensitive Than Creatinine for Detecting Early Renal Impairment in Patients With Diabetes. American Journal of Kidney Diseases, 38(2 (August)), (2001) 310-6. https://doi.org/ 10.1053/ajkd.2001.26096.